Penambahan Tepung Kunyit dalam Pakan Buatan Terhadap Pertumbuhan Ikan Kerapu Cantang (Epinephelus fuscogutattus x Epinephelus lanceolatus) - Sanda Guntara Sanda; Shavika Miranti; Dwi Septiani Putri (Intek Akuakultur, 2022)
This research was carried out from April to June 2021 in Madong Village, Bugis Village, Tanjungpinang City. The purpose of this study was to determine the effect of adding turmeric flour to feed on the growth of cantang grouper. This study used a completely randomized design method with 4 treatments with each treatment repeated 3 times, namely treatment K (without the addition of turmeric flour), treatment A (addition of 10 g of turmeric flour to 1 kg of feed), treatment B ( addition of 15 g of turmeric flour to 1 kg of feed), treatment C (addition of 20 g of turmeric to 1 kg). The results showed that treatment B (addition of turmeric flour 15 g to 1 kg of feed) was the highest treatment for all parameters which included absolute weight growth value of 53.37 g, daily growth rate of 1.19gr/day, feed efficiency 71.48%. However, it was not significantly different from treatment A (addition of 10 g of turmeric flour to 1 kg of feed) which included an absolute weight growth value of 51.66 g, daily growth rate of 1.15 g/day, feed efficiency 65.55%. So, the addition of 10 g of turmeric flour to 1 kg of feed was effective for the growth of Epinephelus foscoguttatus x Epinephelus lanceolatus grouper.